Review: Biochar from Co-Pyrolysis of Biomass and Plastic - Siti Jamilatun; Zulia Arifah; Erna Astuti; Rahayu Aster; Remmo Sri Ardiansyah (Indonesian Journal of Chemical Engineering, 2023)
Plastic and biomass waste disposal will increase if it is not accompanied by appropriate, efficient, and effective waste treatment. Recent research on the yield of charcoal produced by co-pyrolysis has shown that the product of co-pyrolysis of plastic and biomass raw materials is a beneficial additive with a variety of applications, ranging from soil and water improvement, increasing agricultural yields, fuel cells, supercapacitors, as a support/ catalysts, sustainable chemistry, and carbon sequestration. Therefore researchers need to ensure the quality of the results of co-pyrolysis in the form of biochar obtained from any raw material and process to provide maximum benefits, mainly from biomass and plastic raw materials. This study aims to review the formation of biochar from the co-pyrolysis of plastic and biomass raw materials by examining the raw materials, pyrolysis techniques, and the type of reactor used to identify the appropriate parameters. This review discusses biochar production techniques, pyrolysis technology mechanisms, types of pyrolysis, the type of reactor used, the properties of both biomass and plastic raw materials and the properties of biochar produced from various raw materials for comparison. Biochar will be obtained with maximum yield quality from the results of mixing the raw materials for biomass and plastic and optimal operating conditions. It can be an alternative in the bio-oil and syngas energy sector and reduce carbon emissions.